Optimize production through reservoir rock compaction control - Samsuri, Ariffin; Chuong, Pham Vu (Penerbit UTM Press, 2004)
This paper presents compactional laboratory study based on the various controllable parameters such as wellbore angle, perforation shot density, perforation pattern, and flow rate to determine the effects of these parameters to compaction in order to help optimize production through compaction control. The study was conducted on local sandstone core sample. After the mechanical rock properties were determined, the scaled down models with various borehole angles, perforation shot densities, perforation patterns and flow rates were tested with Servo Controlled Compression Testing Machine (SCCTM) using two techniques; static and dynamic tests. The results show that compaction increases as borehole angle, production flow rate and shot density increase and as perforation pattern changes from spiral to inplane and finally inline. In addition, compaction increases slowly at low effective stress. However when effective stress reaches 30-60% of reservoir rock compressive strength, it increases approximately double and followed by the reduction of total oil recovery to 55-73% of the expected total oil recovery. These results show that it is possible to optimize production rate via minimizing compaction which could be achieved by controlling borehole angle, perforation shot density, perforation pattern and flow rate.